Effects of smoking and smoking cessation on healing after mechanical periodontal therapy - Grossi, S G; Zambon, J; Machtei, E E; Schifferle, R; Andreana, S; Genco, R J; Cummins, D; Harrap, G (The Journal of the American Dental Association (1939), 1997)
This study investigated the effect of cigarette smoking on 143 patients' clinical and microbiological responses to mechanical therapy. Treatment included four to six sessions of subgingival scaling and root planing and instruction in oral hygiene. Results indicate that current smokers have less healing and reduction in subgingival Bacteroides forsythus and Porphyromonas gingivalis after treatment compared to former and nonsmokers, suggesting that smoking impairs periodontal healing. As the healing and microbial response of former smokers is comparable to that of nonsmokers, smoking cessation may restore the normal periodontal healing response.